COMPARATIVE ANALYSIS OF TECHNICAL EFFICIENCY OF ISLAMIC BANKS IN SELECTED LOW-INCOME COUNTRIES OF AFRICA AND ASIA (Journal of Business Management and Accounting, 2022)
Islamic banks in Africa and Asia have been characterised by some technical inefficiencies. The sources (managerial issues or scale of operation) of these inefficiencies still remain a problem of empirical investigation since mixed reports have been given in that regard. This study therefore investigated the sources of inefficiencies by decomposing technical efficiencies of the banks and comparing the components of Islamic banks in the low-income countries of Africa and Asia. Data were collected from annual reports of the selected banks and analysed using both descriptive and inferential statistical tools. Data Envelopment Analysis (DEA) was conducted to estimate the pure technical and scale efficiencies of the banks. The study found that the inefficiency attributable to all the selected banks were due to pure technical efficiency (0.876), which was lower than the mean value of scale efficiency (0.917). That is, the inefficiencies were caused largely by managerial problems rather than operating scale. It was also found that Islamic banks in Asia were more technically efficient than those from Africa in terms of pure technical (0.920>0.827) and scale efficiencies (0.934>0.902). The study concludes that managerial issues such as insufficient competent staff, poor monitoring and so on were the causes of low efficiency attributed to Islamic Banks in Africa. It was thus recommended that Islamic banks in Africa should employ staff members who are competent with requisite knowledge of Islamic finance to improve the pure technical and overall efficiency of the banks.